Be Mature: How to break the mold of spiritual immaturity - and grow up in Christ - Wiersbe, Warren W.; (1929-2019) (United Stated of America, 1978)
Born again is only the beginning! Having Christ as your personal Saviour is only the beginning. After that, you have to grow up! Many problems in our lives are caused by spiritual immaturity. God wants us to grow up, not just grow old. And He has given us the formula to maturity in the Epistle of James.
Keywords: Bible -- James -- Commentaries